"WEAVING HARMONY BETWEEN EDUCATIONAL PHILOSOPHY AND TECHNOLOGICAL INNOVATION: BUILDING AN INCLUSIVE AND ADAPTIVE FUTURE FOR EDUCATION" - yovita, sirmawan (Edukasi Kultura, 2024)
"MERAJUT HARMONI ANTARA FILSAFAT PENDIDIKAN DAN INOVASI TEKNOLOGI: MEMBANGUN MASA DEPAN PENDIDIKAN YANG INKLUSIF DAN ADAPTIF"